Enhancing Strength and Ductility of Rubberized Concrete Using Low-Cost Glass Jackets - Panumas Saingam; Muhammad Noman; Burachat Chatveera; Gritsada Sua-Iam; Tahir Mehmood; Qudeer Hussain; Mohammad Alameri; Panuwat Joyklad (Polymers, 2026)
= 0.80-0.99). The proposed GCSM jacket system demonstrates high potential as a sustainable and economical alternative for strengthening and retrofitting rubberized concretes, offering improved ductility and energy absorption while supporting circular material utilization. It is noted that the confinement ratio, size of rubberized aggregates, and their percentage replacement of rubberized aggregates should be consistent with the values used in this work in order to use the proposed analytical expressions.
Keywords: Innovative concrete reinforcement materials; Masonry and Concrete Structural Analysis; Structural Behavior of Reinforced Concrete